The accuracy of a novel image‐guided hybrid robotic system for dental implant placement: An in vitro study. Issue 1 (22nd August 2022) - Tao, Baoxin; Feng, Yuan; Fan, Xingqi; Lan, Kengliang; Zhuang, Minjie; Wang, Shigang; Wang, Feng; Chen, Xiaojun; Wu, Yiqun
Abstract: Background: This in vitro study aims to evaluate the accuracy of dental implant placement by a novel image‐guided hybrid robotic system for dental implant surgery (HRS‐DIS). Methods: The HRS‐DIS with a 5 degree of freedom (DOF) serial manipulator and a 6 DOF Stewart platform was developed. To evaluate the accuracy of repeated drilling, the holes were prepared twice with a 2.2 mm drill. To evaluate the accuracy of dental implant placement, the entry, exit and angle deviations of dental implants were measured. Results: Twenty‐four holes were prepared twice, and mean (±SD) of diameters were measured as 2.2 ± 0.02 mm. A total of 160 dental implants were placed in 32 phantoms by HRS‐DIS. The mean (±SD) of the entry, exit and angle deviation were 0.8 ± 0.54 mm, 0.87 ± 0.54 mm and 1.0 1 ± 0.44°, respectively. Conclusions: The results of the in vitro study preliminarily validated that the HRS‐DIS could provide a high accuracy for dental implant surgery.